ZINC OXCIDE (Web of Teachers: Inderscience Research, 2025)
The rapid growth of the world population, intensifying industrialization, and increasing environmental challenges are raising the global demand for renewable energy sources. Among these, solar energy is considered one of the most promising and environmentally friendly alternatives. In particular, solar photovoltaic systems provide the possibility of generating stable, affordable, and clean electricity without harming the environment. The role of modern photovoltaic technologies in ensuring continuous, efficient, and eco-friendly energy supply for the population is invaluable, and their improvement and adaptation to local climatic conditions remain important scientific and practical tasks. Zinc oxide is a well-known compound that has long been widely used in various fields of industry, technology, and medicine. ZnO thin films are weather-resistant, chemically inert, and transparent in the visible and infrared regions of the spectrum. They are used as electrical contacts, reflective coatings for thin-film solar cells, and components in touch screen displays.